2005
DOI: 10.1128/iai.73.8.4596-4606.2005
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Stimulates Staphylococcus aureus Biofilm Formation

Abstract: Heparin, known for its anticoagulant activity, is commonly used in catheter locks. Staphylococcus aureus, a versatile human and animal pathogen, is commonly associated with catheter-related bloodstream infections and has evolved a number of mechanisms through which it adheres to biotic and abiotic surfaces. We demonstrate that heparin increased biofilm formation by several S. aureus strains. Surface coverage and the kinetics of biofilm formation were stimulated, but primary attachment to the surface was not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
184
1
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(196 citation statements)
references
References 64 publications
4
184
1
7
Order By: Relevance
“…Instillation of high-concentration heparin remains the most common method of "locking" a catheter since it was introduced in the early 1970s. There is evidence that heparin stimulates the growth of biofilm in vitro and higher concentrations of heparin increase biofilm faster than lower concentrations [57]. However, a major complication of heparin locks, especially in the perioperative period, is bleeding due to unsuspected anticoagulation [58].…”
Section: B Preventing Contamination Of the Catheter Hubmentioning
confidence: 99%
“…Instillation of high-concentration heparin remains the most common method of "locking" a catheter since it was introduced in the early 1970s. There is evidence that heparin stimulates the growth of biofilm in vitro and higher concentrations of heparin increase biofilm faster than lower concentrations [57]. However, a major complication of heparin locks, especially in the perioperative period, is bleeding due to unsuspected anticoagulation [58].…”
Section: B Preventing Contamination Of the Catheter Hubmentioning
confidence: 99%
“…The use of heparin is not risk free and in certain instances may actually cause harm, including infection (Shanks et al, 2005) and heparininduced thrombocytopenia (HIT) (Barclay et al, 2012). Additionally, treatments for diseases such as cancer involve the use of medications that can affect coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported a higher frequency of hemorrhagic complications after placement of a new dialysis catheter in patients receiving a high-concentration heparin lock (7). Higher heparin concentrations have also been implicated in promoting the formation of Staphylococcus aureus biofilm (8,9). On the basis of these observations, a recent position paper recommended that a 1000 units/ml heparin solution be adopted as the standard concentration for locking hemodialysis catheters (10).…”
mentioning
confidence: 99%